Case Report: Microincision Vitreous Surgery Induces Bleb Failure in Eyes With Functional Filtering Bleb - Oogi, Satomi; Nakakura, Shunsuke; Asaoka, Ryo; Terao, Etsuko; Dote, Saki; Matsuya, Kanae; Kimura, Yui (Frontiers in Medicine, 2022)
Purpose To investigate the effect of microincision vitreous surgery (MIVS) on intraocular pressure (IOP) control in glaucomatous eyes with functional filtering bleb. Methods We enrolled 18 patients (15 males; median age, 73 years) who previously had filtering surgery and underwent MIVS with functional filtering bleb. Kaplan–Meier method was used to calculate the survival rate with defined the failure as when more number of preoperative antiglaucoma medication was started or additional glaucoma surgery including bleb revisions were performed, and IOP increase of 20% (criteria 1) and 30% (criteria 2) from preoperative levels after 2 weeks of MIVS. Results The median follow-up duration was 970 days. Preoperative IOP was 13.3 ± 3.8 mmHg (mean ± SD). Postoperative IOP were 14.7 ± 4.9 (P=0.365), 15.2 ± 3.5 (P=0.137), 16.4 ± 5.6 (P = 0.073), 17.6 ± 6.1(P = 0.020), and 14.5 ± 4.0 (P = 0.402) mmHg at 3, 6, 12, and 15 months and final visit, respectively (compared to preoperative IOP). The number of antiglaucoma medications was a median of 1.0 (range 0–4) preoperatively and 0 (0–4) at the final visit (P = 0.238). The survival rates were 55%/61% at 3 months, 50%/61% at 6 months, and 38%/55% at 12 months with criteria 1 and 2, respectively. Four eyes (22%) received additional glaucoma surgery during follow-up. Conclusion After several months of MIVS, IOP was likely to increase. We should focus on IOP control by conducting long-term follow-ups.